2004
DOI: 10.1128/jcm.42.3.1316-1318.2004
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation of Borrelia lusitaniae from a Human Patient

Abstract: The first human isolate of Borrelia lusitaniae recovered from a Portuguese patient with suspected Lyme borreliosis is described. This isolate, from a chronic skin lesion, is also the first human isolate of Borrelia in Portugal. Different phenotypic and molecular methods are used to characterize it

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 11 publications
1
106
0
3
Order By: Relevance
“…That group comprises the species B. burgdorferi sensu stricto, B. afzelii, and B. garinii, which are usually transmitted by the vector Ixodes ricinus. Furthermore, there have been reports of B. valaisiana, B. lusitaniae, and B. spielmanii being detected in samples of human skin and cerebrospinal fluid (5,7,30), which suggests that those three species can also give rise to LB. It is often hard to distinguish the clinical symptoms of LB from those of other diseases (10), and hence, it can be difficult to establish a correct diagnosis, especially if the patient is unable to recall having a tick bite.…”
mentioning
confidence: 99%
“…That group comprises the species B. burgdorferi sensu stricto, B. afzelii, and B. garinii, which are usually transmitted by the vector Ixodes ricinus. Furthermore, there have been reports of B. valaisiana, B. lusitaniae, and B. spielmanii being detected in samples of human skin and cerebrospinal fluid (5,7,30), which suggests that those three species can also give rise to LB. It is often hard to distinguish the clinical symptoms of LB from those of other diseases (10), and hence, it can be difficult to establish a correct diagnosis, especially if the patient is unable to recall having a tick bite.…”
mentioning
confidence: 99%
“…Moreover, a recent study indicated that the inoculation of B. lusitaniae into susceptible mice induced pathological features (45). Finally, B. lusitaniae was recently isolated, for the first time, from a chronic skin lesion in a Portuguese patient (5). If this species is actually pathogenic for humans, the risk of Lyme borreliosis must be underlined in North Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have identified Borrelia lusitaniae as a potential agent of Lyme disease. The first human isolate of B. lusitaniae was identified in a 46-year-old woman from the Lisbon area in Portugal (Collares-Pereira et al 2004). Such genospecies are the most prevalent in the Mediterranean area (Collares-Pereira et al 2004;Sarih et al 2003;Younsi et al 2005) and recent studies indicate lizards as the reservoir hosts (Amore et al 2007;Majlathova et al 2006;Richter and Matuschka 2006;Tomassone et al 2005;Younsi et al 2005).…”
Section: Introductionmentioning
confidence: 99%